In-vitro Study: Camp Overshoot Caused by Chronic Morphine Alleviated by the Synergistic Combination of Zamzam Water and Methadone in Human Primary Glioblastoma Cell Line (U-87 MG) - Halim, Shariff; Mohamad, Nasir; PM, Ridzuan; Zakaria, Nur Husna; Muhammad, Nur Atikah (IIUM Medical Journal Malaysia, 2019)
Introduction: Zamzam water is blessed water originated from Mecca and is believed by Muslims to have the ability to cure illness. This ability to cure illness is due to the fact that zamzam water has higher concentration of minerals especially sodium, calcium and magnesium which play a vital role. Sodium is reported to be involved in the regulation of the Mu-Opioid Receptor, which indirectly leads to the production of cAMP. Hence, this current study was carried out to investigate the synergistic effects of zamzam water and methadone combination on cAMP levels in human primary glioblastoma cell line (U-87 MG) after chronic morphine administration. Materials and Methods: The time course and concentration of morphine on U-87 MG cell line was determined. The U-87 MG cell line was incubated with morphine (25 µL/mL) for 24h, to make the cell dependent on morphine and later treated with different combinations of 3.2 mL of zamzam water and methadone (5, 10, 25 µL/mL). The levels of cAMP was determined using the enzyme-linked immunosorbent assay kit. Results: The result revealed that 3.2 mL of zamzam water incubated with 10 µl/ mL of methadone significantly prevented the overshoot production of cAMP level (p<0.05) in U-87 MG cell line after 48h incubation when compared to the untreated samples. Conclusion: These finding suggest that co-treatment with zamzam water and methadone could possibly avoid tolerance and dependence on chronic morphine treatment by preventing the up-regulation of cAMP level.><0.05 in U-87 MG cell line after 48h incubation when compared to the untreated samples. Conclusion: These finding suggest that co-treatment with zamzam water and methadone could possibly avoid tolerance and dependence on chronic morphine treatment by preventing the up-regulation of cAMP level.